Motif Perempuan Menjadi Kepala Sekolah di Sekolah Luar Biasa Kota Surabaya - Athaya, Salsabila (Paradigma, 2022)
Women who are entangled in social construction, make it seem as if women have to be involved only in the domestic sphere. When women are in the public sphere, they are often underdeveloped. There is a lot of stigma that makes women avoid getting a high position, even though they get the opportunity to be beaten by men. Meanwhile, when women get the same opportunities as men, women can also work well like men. This opportunity is obtained by many women in special education. They can become principals, who lead the school and all its contents. Seeing this, this study aims to analyze the motives of women to become principals in special schools. This study uses Alfred Schutz's foundation, to analyze women's motives in choosing to become school principals. The method used is a qualitative approach. The subjects of this study were female school principals in the city of Surabaya with various lengths of office and school backgrounds. The results of this study are based on because of motive, namely the nature of loyalty, encouragement from the foundation, support from family and co-workers. Meanwhile, based on in order to motive, namely improving educational facilities for students, developing schools, and expanding the network of relationships. This known motive shows when women who get support from their surroundings will have more confidence in themselves. When women lead they will show their maximum leadership. Key Word: Fenomenology, Social Motive, Female, Principal, Special School